2016
DOI: 10.1007/s00221-015-4531-2
|View full text |Cite
|
Sign up to set email alerts
|

In Parkinson’s disease on a probabilistic Go/NoGo task deep brain stimulation of the subthalamic nucleus only interferes with withholding of the most prepotent responses

Abstract: The evidence on the impact of subthalamic nucleus deep brain stimulation (STN-DBS) on action restraint on Go/NoGO reaction time (RT) tasks in Parkinson’s disease (PD) is inconsistent; with some studies reporting no effect and others finding that STN stimulation interferes with withholding of responses and results in more commission errors relative to STN-DBS off. We used a task in which the probability of Go stimuli varied from 100 % (simple RT task) to 80, 50 and 20 % (probabilistic Go/NoGo RT task), thus alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 38 publications
2
31
0
Order By: Relevance
“…Importantly, patients' performance improved when they were tested in the on medication/on stimulation condition several months after surgery. Coherently with our findings, STN-DBS has been found to be associated with deficits in go/no-go tasks (Hershey et al, 2004(Hershey et al, , 2010Georgiev et al, 2016but see van den Wildenberg et al, 2006. To our knowledge, this is the first study in which patients' performance has been assessed before and after surgery in two conditions, and in which lesion and stimulation effects have been disentangled.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 59%
See 1 more Smart Citation
“…Importantly, patients' performance improved when they were tested in the on medication/on stimulation condition several months after surgery. Coherently with our findings, STN-DBS has been found to be associated with deficits in go/no-go tasks (Hershey et al, 2004(Hershey et al, , 2010Georgiev et al, 2016but see van den Wildenberg et al, 2006. To our knowledge, this is the first study in which patients' performance has been assessed before and after surgery in two conditions, and in which lesion and stimulation effects have been disentangled.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 59%
“…Moreover, STN-DBS or subthalamotomy in Parkinson's disease can be associated with behavioural and psychiatric problems that reflect deficits in inhibitory control or with the appearance of impulse control disorders (see Jahanshahi et al, 2014;Balarajah & Cavanna, 2013). For instance, several studies in which go/no-go paradigms were used reported that STN-DBS impairs the ability to withhold responses on no-go trials (Hershey et al, 2004(Hershey et al, , 2010Ballanger et al, 2009;Georgiev et al, 2016; but see also van den Wildenberg et al, 2006). To our knowledge, no research until now has examined the role of impulsivity in weight gain after STN-DBS.…”
Section: A N U S C R I P Tmentioning
confidence: 96%
“…Variability in STN DBS-induced impulsive errors also depends on the prepotency of the go reaction and the time pressure to make decisions, further pointing to a role for STN DBS in adjusting response and decision thresholds (Georgiev et al, 2016; Jahanshahi et al, 2015). Future studies manipulating speed-accuracy instructions or the probabilities of corresponding and non-corresponding Simon task trials combined with dorsal and ventral stimulation could provide further insight about the role of DBS to STN subregions in modulating proactive control of strong response impulses.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the well-functioning of neostriatum allows the construction of automaticity, i.e., the control of a learned task with minimal attentional demand [64,48,24]. Other more recent studies in healthy individuals [16] and PPD have confirmed that neostriatum circuits are associated to implicit sequence learning [62,54,23,26] and probabilistic implicit sequences learning [61,63,21]. Therefore, as expected, a tool developed to be sensitive to implicit sequence learning, isolating the influence of motor and EL components, had to be more efficient than a general cognitive test as MoCA to predict the decline in automaticity associate to PD, a disease that has as main pathogenic mechanism dopamine depletion in basal ganglia circuits.…”
Section: Discussionmentioning
confidence: 98%